Mycochemical screening, antioxidant, and cytotoxic properties of Panaeolus cyanescens - KHEA V. GALAY; SHEILA MARIE Y. PLIMACO (Smujo International, 2025)
Abstract. Galay KV, Plimaco SMY. 2025. Mycochemical screening, antioxidant, and cytotoxic properties of Panaeolus cyanescens. Nusantara Bioscience 17: 137-154. This study focuses on exploring the subtleties of the hallucinogenic mushroom Panaeolus cyanescens Sacc., known for its psychoactive component psilocybin. The study focuses on exploring the phytochemical, antioxidant, and cytotoxic properties of ethanolic extracts through rigorous procedures while considering factors such as chemical composition, physiological characteristics, possible therapeutic applications, and the broader implications of its psychoactive nature. The methods used are mycochemical screening, Gas Chromatography-Mass Spectrometry (GC-MS) analysis, DPPH free radical scavenging assay, and brine shrimp lethality test. The goal of the study is to determine the bioactive components in the mushroom and investigate their potential therapeutic applications, with an emphasis on their anticancer capabilities. The process entails gathering, confirming, and producing the extracts. A wide spectrum of secondary metabolites, including flavonoids, steroids, alkaloids, and fatty acids, are shown in the results, suggesting several potential therapeutic advantages. 25 unique compounds with antibacterial, antioxidant, anticancer, and anti-inflammatory properties have been identified by GC-MS analysis, offering a comprehensive understanding of their bioactivity. With an IC50 value of 91.19 ppm, the DPPH assay exhibits strong antioxidant qualities and notable concentration-dependent antioxidant activity. With an LC50 value of 26.63 ppm, cytotoxicity studies show substantial toxicity and strong anticancer effects. The study highlights P. cyanescens's varied bioactive properties, antioxidant capacity, and intriguing anticancer potential while offering crucial insights into the proper dosage and responsible usage of the plant. The findings of the present assessment provide initial scientific validation for the mushroom's historic use in long-standing cultural customs. This study catalyzes additional research and confirmation of its therapeutic value.